Polyclonal activation of human lymphocytes by Bacillus firmus and its constituents - Prokesová, L; Julák, J; Nováková, M; Pospísil, M; Mára, M (Folia microbiologica, 1995)
Bacillus firmus strongly stimulates Ig synthesis in the cultures of human peripheral blood mononuclear leukocytes. As apparent from the character of Ig formation and blastic transformation, the stimulation has features of a polyclonal activation of B lymphocytes without substantial participation of T lymphocytes. B firmus is a strong B cell polyclonal activator even for human cord blood lymphocytes. The most striking feature is the strong stimulation of IgA synthesis in both adult and cord blood lymphocytes. Several crude fractions were isolated from B. firmus. None of them exhibited any remarkable enhancement of activity but the cytoplasmic fraction P-40 was clearly more potent than the intact bacilli. On the other hand, cell wall peptidoglycan, a well known polyclonal activator of B cells, had a much lower activity than whole bacteria. The effect of B. firmus on the stimulation of Ig formation is thus relatively complex; it is not caused mainly by peptidoglycan but rather by some cytoplasmic constituents of the bacterium.
Keywords: Bacillus; Antibodies, Bacterial; Fetal Blood; Adult; protilátky bakteriální; dospělí; Peptidoglycan; stárnutí; aktivace lymfocytů; Humans; fetální krev; lidé; Lymphocyte Activation; peptidoglykan; Aging; B-Lymphocytes; B-lymfocyty